Diagnóstico de la comunicación del Gobierno Descentralizado del cantón Calvas y propuesta de un programa de Relaciones Públicas - Ochoa Torres, Jorge Raúl (2014)
This document is a total study of how it has been doing communications inside and out of Autonomous Government Decentralized of the Canton Calvas and through an exhaustive diagnostic of communication determined its potentialities and weaknesses within this theme, then it was made a proposal of a public relations program according to the actual request of communication supported in technology and modern resource that can be used to get best efficiency and efficacy in the image and the GADCC's public relations. The present work compiles quantitative and qualitative information of how are the communications from the Unit of Public Relations of the GADCC, in front of the different people, where it is determined some fallacies such as: An inopportune communication, a lot of work for the only person who works at the unit, little knowledge for part of Mr. Mayor, in the handling of public relations, etc. Reason for which, it was very opportune make a proposal about Public Relations Program to improve step by step the communications for the benefit of the internal and external publics and all the collectivity.